2018
DOI: 10.3389/fpsyg.2017.02339
|View full text |Cite
|
Sign up to set email alerts
|

The Emotional Modulation of Facial Mimicry: A Kinematic Study

Abstract: It is well-established that the observation of emotional facial expression induces facial mimicry responses in the observers. However, how the interaction between emotional and motor components of facial expressions can modulate the motor behavior of the perceiver is still unknown. We have developed a kinematic experiment to evaluate the effect of different oro-facial expressions on perceiver's face movements. Participants were asked to perform two movements, i.e., lip stretching and lip protrusion, in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
(59 reference statements)
0
3
0
1
Order By: Relevance
“…Indeed, the exposure to congruent facial expressions was found to affect the recognition of hand gestures (Vicario and Newman, 2013), as the observation of facial gesture interferes with the production of a mouth posture involving the same muscles (Tramacere et al, 2018).…”
Section: Motor Signs In Emotional Communicationmentioning
confidence: 99%
“…Indeed, the exposure to congruent facial expressions was found to affect the recognition of hand gestures (Vicario and Newman, 2013), as the observation of facial gesture interferes with the production of a mouth posture involving the same muscles (Tramacere et al, 2018).…”
Section: Motor Signs In Emotional Communicationmentioning
confidence: 99%
“…It has been reported that the change in velocity and duration of oral commissure movement 21 or activity of related muscle, that is, zygomaticus majors, 22 have different meanings in transmitting emotions. Furthermore, it has been shown that the velocity of oral commissure after facial transplantation increases with the clarity of articulation in the later stages of recovery 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Assim, logrou-se testá-la fazendo uso de pacientes com paralisia completa dos movimentos voluntários faciais. Estes foram convidados a reconhecer expressões faciais emocionais em fotos, e apresentaram um desempenho negativo na tarefa que envolve a ativação da musculatura facial, o mimetismo, um mecanismo de simulação de alto nível, crucialmente envolvido na atribuição explícita de emoções (Blom, Aarts, Kunst, Wever, & Semin, 2021;Rymarczyk, Żurawski, Jankowiak-Siuda, & Szatkowska, 2018;Tramacere, Ferrari, Gentilucci, Giuffrida, & De Marco, 2018).…”
Section: Imitação De Expressões Faciais Emocionaisunclassified